(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The Mid-Day Meal Programme (MDMP) is a government initiative aimed at improving the nutritional status of school children in India. This paper examines the health impact of the MDMP on participating children. Through a comprehensive review of existing literature, this study explores the effects of the programme on various health outcomes such as nutritional status, growth, cognitive development, and overall well-being. The findings suggest that the MDMP has a positive impact on the nutritional intake of children, leading to improvements in growth parameters and cognitive functioning. Additionally, the programme has been associated with increased school attendance and performance, further contributing to overall health and development. However, challenges such as quality control, infrastructure, and sustainability remain pertinent. Overall, the MDMP plays a crucial role in addressing malnutrition and promoting the health of school children in India.